Exploring the Hydraulic Failure Hypothesis of Esca Leaf Symptom Formation. Issue 3 (27th August 2019) - Bortolami, Giovanni; Gambetta, Gregory A.; Delzon, Sylvain; Lamarque, Laurent J.; Pouzoulet, Jérôme; Badel, Eric; Burlett, Régis; Charrier, Guillaume; Cochard, Hervé; Dayer, Silvina; Jansen, Steven; King, Andrew; et al.
Abstract : Leaf scorch symptom development is associated with the disruption of vessel integrity. Abstract: Vascular pathogens cause disease in a large spectrum of perennial plants, with leaf scorch being one of the most conspicuous symptoms. Esca in grapevine ( Vitis vinifera ) is a vascular disease with huge negative effects on grape yield and the wine industry. One prominent hypothesis suggests that vascular disease leaf scorch is caused by fungal pathogen-derived elicitors and toxins. Another hypothesis suggests that leaf scorch is caused by hydraulic failure due to air embolism, the pathogen itself, and/or plant-derived tyloses and gels. In this study, we transplanted mature, naturally infected esca symptomatic vines from the field into pots, allowing us to explore xylem integrity in leaves (i.e. leaf midveins and petioles) using synchrotron-based in vivo x-ray microcomputed tomography and light microscopy. Our results demonstrated that symptomatic leaves are not associated with air embolism. In contrast, symptomatic leaves presented significantly more nonfunctional vessels resulting from the presence of nongaseous embolisms (i.e. tyloses and gels) than control leaves, but there was no significant correlation with disease severity. Using quantitative PCR, we determined that two vascular pathogen species associated with esca necrosis in the trunk were not found in leaves where occlusions were observed. Together, these results demonstrate that symptom development is associated with the disruption of vessel integrity and suggest that symptoms are elicited at a distance from the trunk where fungal infections occur. These findings open new perspectives on esca symptom expression where the hydraulic failure and elicitor/toxin hypotheses are not necessarily mutually exclusive.